Gender differences in inflation expectations: Recent evidence from India - Swapnil Virendra Chalwadi; Preeti Tushar Joshi; Nitin Mohanlal Sharma; Chaitanya Gite; Sangita Salve (Administrative Sciences, 2023)
This study investigates gender disparities in inflation expectations in India using data from the Reserve Bank of India's Households' Inflation Expectations Survey (March 2011 to September 2022). To determine these differences, the authors analyze the expectations of future prices for various categories including food products, nonfood products, household durables, housing, and general prices for both a short-term horizon (the next three months) and a long-term horizon (one year ahead). The authors employ independent sample t test, ordinary least square (OLS) regression, and ordinal logistic regression (OLOGIT) models to assess the average inflation expectations disparities between genders. The results demonstrate a significant relationship between gender and inflation expectations, with the findings indicating that, on average, females exhibit higher inflation expectations compared to males.
Keywords: 350; gender; India; inflation perception; monetary policy